Knowledge and Attitudes of Parents about Oral Health in the Primary Dentition Stage in a Peruvian High Andean City. - Rojas Briceño, Nilton Beltrán (2024)
Children’s oral health depends on parents’ knowledge and attitudes. The primary dentition stage, in particular, plays a crucial role in the comprehensive development of children. Therefore, the objective was to evaluate parents’ knowledge and attitudes about oral health in the primary dentition stage in Chachapoyas (Amazonas, NW Peru). A questionnaire was administered to 409 parents from 15 educational institutions, and the data were analyzed using multinomial logistic regression. Among the surveyed parents, 75.3% could identify at least one habit harmful to their children’s teeth (such as excessive sugar consumption) and one of its effects (such as dental caries). Additionally, 77.5% reported that their children presented some dental problem, more frequent in the peripheral areas than in the city’s center. Gender (odd ratio, OR = 0.484; p = 0.037), educational level (OR = 2.144; p = 0.043), and type of health insurance (OR = 2.627; p = 0.044) of the parents influenced awareness of taking care of their children’s primary dental health. The geographic location of the school (1.729 < OR < 2.079; p ≤ 0.011) and family income (OR = 3.504; p = 0.028) influenced parents’ identification of the different harmful effects of children’s habits. Factors such as low socioeconomic status and never taking the child to the dentist increased the risk of dental problems (p < 0.05). It is suggested that peripheral areas, like rural areas, lack the same oral health programs and access to treatment as central urban areas, leading to disparities in parental knowledge and attitudes. © 2024 by the authors.